Marginalisasi dan Subordinasi pada Perempuan Pekerja Industri Kimia di Kecamatan Krian - Kusnah, Faridhatul; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
Patriarchal culture still developing in various aspects of life, one of which is the aspect of work. In terms of work, it is not spared from the influence of patriarchal culture, as happened to women workers in the chemical industry